[Lava Flow at Hekla] - Streng, Evelyn Fiedler (1970)
Photograph of a lava flow at Hekla. The black, stacked rocks form a wall along the grey, rocky ground. A person in an orange vest and a person in a brown jacket stands beside the wall, looking at the rocks.